Life Prediction of Flexspline based on the Modified P-S-N Curve - Qingwen Huang; Baisheng Wu; Delin Liao (Jixie chuandong)
By using Hypermesh to mesh the harmonic reducer and utilizing Abaqus to complete its transient analysis. Based on the results of transient analysis，the position of the dangerous point of the flexspline is determined，a method of extracting and synthesizing the stress spectrum of the dangerous point of the flexspline is proposed. By counting the rain flow of the stress spectrum，combining the modified P-S-N curve and Miner theory，the life of the flexspline of the harmonic reducer is predicted. The predicted result agrees with the life of domestic harmonic reducer products. This work will provide a reference for the quantitative evaluation of the fatigue performance of the flexspline of the harmonic reducer.